Oral drug therapy following bariatric surgery: an overview of fundamentals, literature and clinical recommendations. (22nd June 2016) - Azran, Carmil; Wolk, Omri; Zur, Moran; Fine‐Shamir, Noa; Shaked, Gad; Czeiger, David; Sebbag, Gilbert; Kister, Olga; Langguth, Peter; Dahan, Arik
Summary: Bariatric surgery is the most effective solution for severe obesity and obesity with comorbidities, and the number of patients going through bariatric surgery is rapidly and constantly growing. The modified gastrointestinal anatomy of the patient may lead to significant pharmacokinetic alterations in the oral absorption of drugs after the surgery; however, because of insufficient available literature and inadequate awareness of the medical team, bariatric surgery patients may be discharged from the hospital with insufficient instructions regarding their medication therapy. In this article, we aim to present the various mechanisms by which bariatric surgery may influence oral drug absorption, to provide an overview of the currently available literature on the subject, and to draw guidelines for the recommendations bariatric surgery patients should be instructed before leaving the hospital. To date, and until more robust data are published, it is essential to follow and monitor patients closely for safety and efficacy of their medication therapies, both in the immediate and distant time post‐surgery.